Immunomodulation of the innate immune system: The role of vitamin D in the context of monocytes and macrophages - Mol, Bronwyn Ashleigh (University of the Witwatersrand, Johannesburg, 2024)
Macrophages are widely distributed cells of the innate immune system with essential roles in homeostasis and disease. Despite concerted efforts, several aspects of macrophage origin, biology, and functionality remain poorly understood. To gain a deeper understanding of these cells, a physiologically relevant, but practical model is required. In vitro, macrophages are principally generated from primary monocytes and monocyte-like cell lines through a natural process referred to as monocyte-to-macrophage differentiation. Monocyte-like cell lines have several practical advantages over the use of primary monocytes with the most commonly employed monocyte-like cell lines being THP-1 and U937 cells. Despite their frequent use, no standardised protocol is employed in the differentiation of monocyte-like cell lines to macrophages. Naturally, this results in large discrepancies and a lack of comparability between studies. Furthermore, many of these protocols are not physiologically relevant and produce macrophages that are not responsive to downstream stimuli. 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), the biologically active form of vitamin D3, is a recognised immunomodulator that shows pronounced genomic and non-genomic effects in immune cells. It is also reported as an inducer of monocyte-to-macrophage differentiation, though heavily debated, and a potential macrophage polarisation agent. Despite this, there is relatively little information concerning the role of 1,25(OH)2D3 in monocyte-to-macrophage differentiation and macrophage biology. This study aimed to develop a more physiologically relevant differentiation protocol for the monocyte-like THP-1 and U937 cell lines. This model was then used to investigate the role of 1,25(OH)2D3 in monocyte-to-macrophage differentiation and macrophage biology. Assessment of morphological features and the macrophage markers, CD11b and CD14, indicated that in both THP-1 and U937 cells, differentiation induced using a combination of 5 nM of phorbol 12-myristate 13-acetate (PMA) and 10 nM 1,25(OH)2D3 over 96 hours produced the most mature macrophages. It was observed that 1,25(OH)2D3 alone was not capable of inducing differentiation, yet when combined with PMA, greatly enhanced macrophage features. THP-1 cells are the most widely employed monocyte-like cell line, and are proposed to be the most reflective of primary monocytes. In this study these cells were shown to be more responsive to the effects of 1,25(OH)2D3 than their U937 counterparts. As such, RNA-sequencing was used to explore the efficacy of the proposed differentiation protocols and the influence of 1,25(OH)2D3 on macrophage biology in THP-1 cells. Differential gene expression analysis confirmed that the most effective differentiation protocol was the combination of 5 nM PMA with 10 nM 1,25(OH)2D3 when considering macrophage associated features including transcription factor usage, adhesion, phagocytosis, and cytokine and cytokine receptor expression. This protocol also produced THP-1-derived macrophages that showed increased expression of genes considered to be primary macrophage markers. These results also suggested that THP-1 cells differentiated with neither PMA nor PMA with 1,25(OH)2D3 were likely to represent fully polarised macrophages. 1,25(OH)2D3 treatment of THP-1 monocytes and THP-1-derived macrophages produced distinct gene expression profiles with considerably less overlap than expected. Though 1,25(OH)2D3 treatment often affected similar biological processes in both cell types, the genes within these processes found to be differentially expressed in each cell line were often distinct. For example, in THP-1- derived macrophages, but not THP-1 monocytes, 1,25(OH)2D3 treatment resulted in the increased expression of genes encoding numerous antibacterial peptides, several small GTPases and their regulators. Additionally, several type I interferon response related proteins showed decreased expression, while expression of cytokines and cytokine receptors was variable. This, taken together with the morphological work, indicates two potential roles for 1,25(OH)2D3 in macrophages. Firstly, a protective role as it suggests the potential to prime an antibacterial response, while still balancing inflammatory responses and protecting against autoinflammation induced by aberrant type I interferon response. Secondly, a potential role in determining the morphological features, clearly demonstrated through microscopy, and further suggested by the differential expression of a variety of small GTPases and their regulators.
A thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Monocytes; Macrophages; THP-1; Vitamin D; 1; 25-dihydroxyvitamin D3; Immunomodulation; Monocyte-to-macrophage differentiation; Phorbol 12-myristate 13-acetate; RNA-sequencing; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education